Fasilitas Yang Sesuai Untuk Anak Yang Ber Kebutuhan Khusus Di Sekolah Inklusi - Siti Nawati; Helipa Loren; Piddiyanti; Opi Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The aim of this research is to determine the importance of appropriate facilities for children with special needs. The method used in this research is a literature review study or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The appropriate and required screening results contained 3 National Journal articles based on the articles found and analyzed. The results of this research are. Educational facilities are all equipment, materials and furniture that are directly used in the educational process at school.In inclusive schools, schools must provide pedagogues who know and understand the education of children with special needs, educational teaching aids for children with special needs, and special spaces needed for children with special needs. To date, the Department of Education has not issued guidelines regarding standard room facilities for inclusive schools, but only has standard room facilities for public schools such as: study rooms, furniture rooms, landscaping rooms, learning equipment, decoration and classrooms and soon.